PEMANFAATAN IMBAL HASIL CASH WAQF LINKED SUKUK - Erlita Nurma Wati; Moh Badrus Sholeh; Muhammad Heru Akhmadi (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Cash Waqf Linked Sukuk (CWLS) is a new breakthrough in government financing based on social investment. The presence of CWLS can develop waqf instruments by integrating three main sectors at once, namely the commercial, fiscal, and Islamic social finance sectors. This study aims to discuss the SW001 series CWLS scheme and determine the relationship between the authorities that play a role in the utilization of cash waqf investment returns invested through State Sukuk by the Indonesian Waqf Board (BWI). BWI consists of the use of returns when making investments for the first time and the utilization and optimization of the CWLS imbalance. The research uses a qualitative method with a case study technique using ATLAS.ti software to assist the coding and data analysis process. The results of this study indicate that there is a close relationship between the authorities who play a role in CWLS. Furthermore, the use of discounts and coupons managed by the Achmad Wardi Eye Hospital was realized in the form of waqf assets in the form of retinas, glaucoma centers and the provision of various free eye surgeries for the poor